2012
DOI: 10.1021/jf304443u
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Germination on Phytochemical Profiles and Antioxidant Activity of Mung Bean Sprouts (Vigna radiata)

Abstract: Epidemiological studies have shown that regular consumption of fruits and vegetables is associated with reduced risk of chronic diseases. It is recommended to increase consumption of fruits and vegetables to prevent chronic diseases related to free radical-induced oxidative stress. Different varieties of fruits and vegetables provide different vitamins, phenolics, flavonoids, minerals, and dietary fibers for optimal health benefits. Mung bean sprouts are one of the major vegetables in human diet. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
206
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(228 citation statements)
references
References 21 publications
19
206
2
1
Order By: Relevance
“…The fastest growth of mung bean occurred on the fifth day and achieved a maximum content of Food Sci., 34, 2016 (1): 68-78 doi: 10.17221/434/2015-CJFS 5.79 mg GAE/g, almost 1.20 fold of the seeds. Guo et al (2012) reported that the TPC of mung bean dramatically increased to 996.4 mg GAE/100 g DW (4.5 fold of the seeds) during 9-day germination. Huang et al (2014) found that the TPC range of germinated mung bean and soybean was 0.41-1.2 and 0.32-0.44 mg GAE/g DW during 5-day germination.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fastest growth of mung bean occurred on the fifth day and achieved a maximum content of Food Sci., 34, 2016 (1): 68-78 doi: 10.17221/434/2015-CJFS 5.79 mg GAE/g, almost 1.20 fold of the seeds. Guo et al (2012) reported that the TPC of mung bean dramatically increased to 996.4 mg GAE/100 g DW (4.5 fold of the seeds) during 9-day germination. Huang et al (2014) found that the TPC range of germinated mung bean and soybean was 0.41-1.2 and 0.32-0.44 mg GAE/g DW during 5-day germination.…”
Section: Resultsmentioning
confidence: 99%
“…The highest values of soybean and black bean were increased by 146.2/133.3% (TRP), 211.0/78.6% (RDSC), and 167.6/90.1% (ARSC), while changes of antioxidant activity varied between and within species. Guo et al (2012) reported that the antioxidant activity of mung bean sprouts was 6 times higher than in the seeds. Pajak et al (2014) observed a more than 10-fold increase of antioxidant activity against ABTS and DPPH radicals in mung bean after 5-day germina- Food Sci., 34, 2016 (1): 68-78 doi: 10.17221/434/2015-CJFS tion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vitamin C (ascorbic acid) content significantly increased in malted ragi, wheat, mung beans, chickpea, and wheat (Desai et al., 2010; Guo, Li, Tang, & Liu, 2012; Laxmi et al., 2015). Vitamin C can be synthesized by plants and animals from glucose, mannose, and galactose (Banhegyi & Mandl, 2001; Wheeler, Jones, & Smirnoff, 1998).…”
Section: Effect Of Germination or Malting On Nutrients And Mineralsmentioning
confidence: 99%